Determinants of exercise capacity in patients with heart failure without left ventricular hypertrophy. Issue 1 (January 2023) - Ishizaka, Suguru; Iwano, Hiroyuki; Tsujinaga, Shingo; Murayama, Michito; Tsuneta, Satonori; Aoyagi, Hiroyuki; Tamaki, Yoji; Motoi, Ko; Chiba, Yasuyuki; Tanemura, Asuka; Nakabachi, Masahiro; Yokoyama, Shinobu; et al.
Abstract: Background: Determinants of exercise intolerance in a phenotype of heart failure with preserved ejection fraction (HFpEF) with normal left ventricular (LV) structure have not been fully elucidated. Methods: Cardiopulmonary exercise testing and exercise-stress echocardiography were performed in 44 HFpEF patients without LV hypertrophy. Exercise capacity was determined by peak oxygen consumption (peak VO2 ). Doppler-derived cardiac output (CO), transmitral E velocity, systolic (LV-s′) and early diastolic mitral annular velocities (e′), systolic pulmonary artery (PA) pressure (SPAP), tricuspid annular plane systolic excursion (TAPSE), and peak systolic right ventricular (RV) free wall velocity (RV-s′) were measured at rest and exercise. E/e′ and TAPSE/SPAP were used as an LV filling pressure parameter and RV-PA coupling, respectively. Results: During exercise, CO, LV-s′, RV-s′, e′, and SPAP were significantly increased ( p  < 0.05 for all), whereas E/e′ remained unchanged and TAPSE/SPAP was significantly reduced ( p  < 0.001). SPAP was higher and TAPSE/SPAP was lower at peak exercise in patients showing lower-half peak VO2 . In univariable analyses, LV-s′ ( R  = 0.35, p  = 0.022), SPAP ( R  = −0.40, p  = 0.008), RV-s′ ( R  = 0.47, p  = 0.002), and TAPSE/SPAP ( R  = 0.42, p  = 0.005) were significantly correlated with peak VO2 . In multivariable analyses, not only SPAP, but also TAPSE/SPAP independently determined peak VO2 even after the adjustment for clinically relevant parameters. Conclusions: In HFpEF patients without LV hypertrophy, altered RV-PA coupling by exercise could be associated with exercise intolerance, which might not be caused by elevated LV filling pressure. Graphical abstract: Unlabelled Image Highlights: We evaluated the mechanisms of exercise intolerance in HFpEF without LVH. In this population, PH and RV to PA uncoupling were associated with exercise capacity. PA distensibility might affect exercise intolerance in HFpEF patients without LVH.